Bioaccumulation of arsenic and uranium in two fish species ( clarias lazera and Tilapia zilli ) from alaro stream in Ibadan, Nigeria (2014)
Studies were carried out on the bioaccumulation of arsenic (As) and uranium (U) in the organs of two fish species (Clarias lazera and Tilapia zilli) from Alaro stream in Ibadan, Nigeria. Fish were collected from the entire Alaro stream downstream of the industrial effluent outfall for six months from July to December using cast and gill nets. Dissections were carried out to remove the gills, fins, gut, liver, bones and muscle for acid digestion. Samples were analyzed using the inductively coupled plasma-mass spectrometer (ICP-MS) with quality assurance of the results obtained using bovine liver standard reference material (SRM) from the National Institute of Standards and Technology (NIST).The results show that As and U levels in the fish organs exceeded the World Health Organization (WHO) guideline limit and other international standards. This indicates that fish caught in Alaro stream is unfit for human consumption since it contains the carcinogens: arsenic and uranium. It is recommended that the polluted stream should be monitored, treated and controlled for food security and other human uses of the stream